2021
DOI: 10.5812/jjnpp.117046
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of Whey Protein-Based Films in Food Products: Emphasis on the Addition of Natural Edible Bio-nanocomposites with Antioxidant and Antimicrobial Activity

Abstract: : Food spoilage is one of the major elements of food insecurity that has acquired significant attention over recent decades due to global human population growth. Several studies have investigated increasing shelf life of food products using natural and environmentally friendly compounds. Whey protein (WP) can be an important additive material because it is well-known for its high value of nutrition and well characteristics for the formation of edible films. Furthermore, natural bioactive compounds have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…This revealed that whey proteins may be able to change the DNA damage caused by elevated iron levels and lessen ROS in cells [ 60 ]. Pseudomonas aeruginosa is one of the recognized microorganisms that cause pulmonary infection and lung colonization, which lead to breathing problems [ 61 ]. Rats fed a pressurized whey protein diet exhibited a reduction in oxidative stressors, inflammation, and lung damage, according to studies on the importance of whey protein in decreasing pulmonary infection by Kishta and his team [ 62 ].…”
Section: Applications Of Whey and Its Bioactive Components In Various...mentioning
confidence: 99%
“…This revealed that whey proteins may be able to change the DNA damage caused by elevated iron levels and lessen ROS in cells [ 60 ]. Pseudomonas aeruginosa is one of the recognized microorganisms that cause pulmonary infection and lung colonization, which lead to breathing problems [ 61 ]. Rats fed a pressurized whey protein diet exhibited a reduction in oxidative stressors, inflammation, and lung damage, according to studies on the importance of whey protein in decreasing pulmonary infection by Kishta and his team [ 62 ].…”
Section: Applications Of Whey and Its Bioactive Components In Various...mentioning
confidence: 99%
“…The microbial activity causes the pH of the sausage to change quickly. To avoid the aforementioned occurrence, it may be required to include supplemental ingredients in some situations, such as whey protein or essential oil [57,116].…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%